2005
DOI: 10.1089/jwh.2005.14.650
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, Behavioral, and Interpersonal Impact of Human Papillomavirus and Pap Test Results

Abstract: An understanding of young women's responses to HPV and Pap test results may help guide clinical interventions designed to prevent possibly harmful psychosocial and interpersonal responses to HPV and Pap testing but promote healthy sexual behaviors and regular screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
2
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 32 publications
7
66
2
9
Order By: Relevance
“…In preliminary studies of both adults and adolescents, HPV testing has been associated with anxiety, distress, perceived stigma, and fear of further testing and treatment procedures. (13,15,16,25) These types of responses may adversely impact adolescent decisions about future STI screening and follow-up. (26,27) Our previous work has demonstrated that cognitive understanding of HPV infection and Pap tests is a key factor in predicting psychosocial and behavioral responses to HPV infection and abnormal Pap tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies of both adults and adolescents, HPV testing has been associated with anxiety, distress, perceived stigma, and fear of further testing and treatment procedures. (13,15,16,25) These types of responses may adversely impact adolescent decisions about future STI screening and follow-up. (26,27) Our previous work has demonstrated that cognitive understanding of HPV infection and Pap tests is a key factor in predicting psychosocial and behavioral responses to HPV infection and abnormal Pap tests.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that these types of negative responses could decrease follow-up for diagnostic or treatment procedures. (13,(15)(16)(17)(18) Education may prevent or alleviate psychosocial distress by addressing women's concerns about HPV. (19) Finally, HPV vaccines have been developed that target the HPV types most commonly associated with cervical cancer, genital warts, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Some participants who did not intend to disclose to their sexual partners tended to be HPV-positive and to view abnormal results as stigmatizing or shameful. The HPV-infected women also reported feeling worse about their past and future sexual relationships (Kahn et al, 2005;McCaffery et al, 2004). Another study that examined the psychological impact on women being tested for HPV also reported that women with borderline or mild dyskaryotic Pap test results who were HPV-infected described more anxiety and distress, and had more interpersonal concerns than women with borderline or mild dyskaryotic smear results who were not HPV-infected (Maissi et al, 2004).…”
Section: Hpv-related Psychosocial Health Outcomesmentioning
confidence: 99%
“…Studies conducted with sexually active young women showed that most participants reported relief or happiness if HPV results were negative, and anxiety or distress if results were positive (Kahn et al, 2005;McCaffery et al, 2004). Some participants used coping mechanisms such as denial of an abnormal test result or its implications.…”
Section: Hpv-related Psychosocial Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation